2020
DOI: 10.1093/jnen/nlaa088
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Primary and Recurrent Glioblastomas Reveals a Reduced Level of Pentraxin 3 in Recurrent Glioblastomas

Abstract: Glioblastomas (GBM) are highly infiltrative tumors and despite intensive treatment tumor recurrence is inevitable. The immune microenvironment in recurrent GBM is poorly characterized, but it is potentially influenced by therapeutic interventions with surgery, radiotherapy, and chemotherapy. The aim of this study was to obtain a deeper insight in the immune microenvironment in primary and recurrent GBM. Primary and recurrent glioblastoma samples from 18 patients were identified and expression profiling of 770 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…The processes of counterstaining, coverslipping, and slide digitization were performed as described above. Automated digital image analysis and quantification were done in the Visiopharm APP author module as previously described (64, 65). Output variables were percentages of positive area, defined as the area of positive expression divided by the total area of interest multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%
“…The processes of counterstaining, coverslipping, and slide digitization were performed as described above. Automated digital image analysis and quantification were done in the Visiopharm APP author module as previously described (64, 65). Output variables were percentages of positive area, defined as the area of positive expression divided by the total area of interest multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%
“…Petterson et al, compared the gene expression between paired pGBMs and rGBMs based on the RNA obtained from formalin-fixed paraffin-embedded (FFPE) tissue sections [26]. Gene set enrichment analysis suggested the expression of genes involved in metabolism, extracellular matrix (ECM) remodeling, and complement activation are lower in rGBMs than pGBMs.…”
Section: Conventional Approach To Elucidate Immune Microenvironment I...mentioning
confidence: 99%
“…Instead, genes related to T cell activation and checkpoint signaling were high in rGBM, suggesting T cell activation is part of the event that promotes the recurrence of GBM progression (we will discuss how this affects GBM in a later part). Moreover, they compared early recurring tumors (shorter than 14 months after primary treatments) with late recurring tumors (longer than 14 months after primary treatments) and found that genes involved in ECM remodeling, angiogenesis, and growth factor signaling are expressed higher, and genes related to Th2 cell activation, chemokine signaling, and tolllike receptor (TLR) are lower in tumors with early recurrence [26]. The differentially expressed genes between early-and late-recurrent tumors must provide useful information for predicting the patient outcome.…”
Section: Conventional Approach To Elucidate Immune Microenvironment I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased synthesis of inflammatory biomarkers and activation of chemokine receptors (mediated through IL-6, IL-8, CX3CL1), leukocyte and stromal cells recruitment, induction of reactive oxidative species, hypoxia, and necrosis have been also identified in glioblastomas—highly aggressive astrocytic tumors [ 45 , 63 ]. Glioma represents one of the most common and lethal tumors in middle-aged and elderly individuals with a poor prognosis due to rapid cellular infiltration and invasiveness [ 64 , 65 ]. Unfortunately, tumor recurrence appears despite tumor resection, intensive healthcare, and treatment [ 63 , 65 ].…”
Section: Glioblastoma and Meningiomamentioning
confidence: 99%